Couvrir la colonisation sans la violence : des femmes journalistes allemandes face à la germanisation à l’Est pendant la Seconde Guerre mondiale - Deborah Barton; Fabien Théofilakis (Genre & Histoire)
AbstractBy focusing on journalism – a profession that the National Socialist regime viewed as critical to the maintenance of the Nazi state -- this article examines representations of the violence that accompanied the German conquest of East Europe and the subsequent Nazi Germanization projects that took place within these regions. The authors outline the historiographical evoluion of women’s involvement in the violence and genocide perpetrated by Nazi Germany and then follow the journey of four women journalists – Ilse Urbach, Liselotte Purper, Renate von Stieda and Helene Rahms – to illustrate the gendered way in which these women reported on processes of extreme violence between 1939 to 1945.